RESTRICTIONS TO FREEDOM OF ASSOCIATION, ASSEMBLY, AND SPREADING OPINION POST CHANGES TO COMMUNITY ORGANIZATIONAL LAW - Sirajul Munir; lailul ilham (Fakultas Hukum Universitas Lampung, 2022)
Protection of Freedom of association, assembly, and expression as recognition of human rights. Through the Community Organization Law, the state regulates the balance in protecting rights without neglecting social responsibility. This balance is regulated as an effort to safeguard the country's sovereignty. This paper uses the following approaches: a) conceptual approach, to look at concepts of law and democracy that are relevant to the research problem; b) statute approach, a juridical normative analytic research approach, the research based on critical thinking by referring to legal sources of the Community Organization Law. This research concludes that Pancasila seeks to build harmony and balance between individual and national interests (society). Therefore, the freedom that exists in Indonesia is not an absolute right. This means that these freedoms are subject to many restrictions established in law. Principlescontrary to Pancasila and the 1945 Constitution of the Republic of Indonesia have triggered the government to expand the prohibition against mass organizations. These principles aim to change the ideological basis of Pancasila and choose to make changes in the mechanism for revoking the status of a legal entity using the principle of contrarius actus to be more effective and efficient in taking action.